Job Insecurity and Employees’ Extra-Role Behavior: Moderated Mediation Model of Negative Emotion and Workplace Friendship - Yu, Shengxian; Wu, Na; Liu, Shanshi; Gong, Xiaoxiao (Frontiers in Psychology, 2021)
Based on the theory of emotional events, this paper discusses the influence of job insecurity on employees' extra-role behaviors. The mediating effect of negative emotions and the moderating effect of workplace friendship are also tested. The results of an empirical analysis, based on the data of 327 employees, show that job insecurity has a significant negative impact on employees' extra-role behaviors. Negative emotions play a mediating role in the relationship between job insecurity and extra-role behaviors. Workplace friendships moderated the relationship between job insecurity and negative emotions, as well as between job insecurity and extra-role behaviors. Workplace friendship also moderates the mediating effect of negative emotions on the relationship between job insecurity and extra-role behaviors. that is, the higher the level of the workplace friendship is, the weaker the mediation role mentioned above will be. The research results have implications for the sustainable development of the organization.